Sustainable multi-products delivery routing network design for two-echelon supplier selection problem in B2B e-commerce platform - Prajapati, Dhirendra; Chelladurai H.; Zhou, Fuli; Ip, Andrew W.H.; Pratap, Saurabh (EDP Sciences, 2022)
This paper examines the environmental impact produced by multi-vehicle transportation on a sustainable supply chain (SC) network. The relevance of green principles is gaining momentum day by day, which has forced the governments to introduce carbon emission schemes for the transportation associated with the firms. Various countries around the globe are introducing carbon-pricing schemes, in which a carbon tax is imposed based on the amount of anthropogenic emissions. A firm, which sets environmental standards for the emission associated with its operational activities, should design a transportation network based on the trade-off between its economic efficiency and the carbon emission. In this paper, the main focus is to design a sustainable supply chain network. A mixed-integer-non-linear-programming (MINLP) model is formulated to minimize the overall cost incurred in a multi-vehicle, multi-product sustainable transportation network. The meta-heuristic approach i.e., Hybrid Chemical Reaction Optimization Algorithm with Tabu search (CRO-TS) and LINGO solver have been used to solve the proposed model. This analysis can guide the government to encourage the logistics service providers to capitalize on anthropogenic gas emission systems and simultaneously design the tax policy on carbon emission.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Carbon emission; Chemical reaction optimization algorithm; LINGO; Multi-vehicle transportation; ustainable transportation network design; Tabu search; Carbon; Costs; Economic and social effects; Environmental impact; Gas emissions; Heuristic methods; Nonlinear programming; Product design; Supply chains; Sustainable development; Tabu search; Vehicles; Carbon emissions; Chemical reaction optimization algorithms; LINGO; Multi-products; Multi-vehicle transportation; Multi-vehicles; Network design; Sustainable transportation; Sustainable transportation network design; Transportation network; Integer programming